Student’s Reversibility in Solving Algebraic Problem - Entya Esa Fitmawati; Tatag Yuli Eko Siswono; Agung Lukito (SAINTIS Publishing, 2019)
Reversibility is a mental process to construct two-way correlation from an initial condition to the result, and from result reverse to initial state. The concept of reversibility is a key aspect of the development of mathematics which is often problema for student. Reversible thinking is the primary requirement to solve mathematical problems. The importance of reversibility is one of the reasons in this study. The aimed of this study was to identify student’s reversibility in solving algebaic problems. The subject consisted of 32 junior high school student’s, especially at the eight grade. In this qualitative study, data were collected by a reversibility task and interview. The reversibility task contained simple equation. The result of this study indicate that reversibility aspect of solving algebaic problem can identified were reciprocity and negation, in this case reciprocity was more prominent. This could be seen from 32 junior high school students were able to make equation according to the reversibility aspect, but there were only five students are be able to fulfill two aspect of reversibility, described as negation and reciprocity, the others only fill reciprocity. The result showed that the problem related reversibility on junior high school still exist, especially in the aspect of negation.